Water mass characteristics in the Makassar Strait and Flores Sea in August-September 2015. Issue 1 (December 2021) - Silaban, L L; Atmadipoera, A S; Hartanto, M T; Herlisman,
Abstract: Makassar Strait is one of the main entrance points for Indonesian Throughflow (ITF), which carries water from the North Pacific through Flores Sea. ITF has a crucial role as a branch of the thermohaline circulation system in controlling the Indonesian marine ecosystem as well as regional climate variability. This research aims to describe the structure and stratification of water mass and the distribution parameters of chemical physics in the area of Makassar Strait up to Flores Sea at the month of August-September 2015 as much as 8 casts of data CTD is obtained from the result of expedition STOKAS BRKP-KKP using research vessel Baruna Jaya VIII. Research results indicate that the origin of the water mass from the North Pacific is still dominant in the thermocline layer (NPSW) also in the intermediate (NPIW). On average the depth of mixed water layers 60m (± 12.59) with temperature variation between 25.62 – 27.65 C, the average depth of thermocline 130m (±43.65) with temperatures between 18.29 °C – 21.88 °C. Temperature, pH, and dissolved oxygen distribution tends to be higher in the northern region. Fluorescence distribution in the south is higher than the northern region due to inputs from the Makassar upwelling.